Coverage and Values of Legal Deposit in Bosnia and Herzegovina (1945–1995) - Lejla Hajdarpašić (Bosniaca)
Goal: Legal deposit is a complex system of multiple benefits, and by mapping adapted legal deposit regulations from 1945 to 1995 in Yugoslavia and Bosnia and Herzegovina, the aim of this research is to look at the development of the legal deposit in the context of redefining its coverage and the legislatively defined goals of the legal deposit. Approach/methodology/design: By researching the previous literature and reviewing official publications, that is examining the titles and full texts of published regulations in the printed editions of official publications, the relevant regulations related to the legal deposit in Yugoslavia, Bosnia and Herzegovina, federal and republican decrees, decisions, orders, laws for legal deposit were mapped. Results: The analysis of the mapped sixteen regulations, indicates the expansion of legal deposit coverage on a continuous basis, and reveals changes in the perception of the legal deposit values. Legal deposit was initially reduced in the regulations to its function of building library collections, which, however, must be viewed critically in the context of censorship background, while newer regulations respect its values in terms of building of national bibliographies, preservation and protection of cultural heritage, and more important, use of materials that have the designation of public good. Originality/value: This research thematizes the development of the legal deposit system in Bosnia and Herzegovina, from 1945 to 1995, by gathering selected regulations related to legal deposit, adopted in this time period, for the first time in one place, as a basis for further research of this institution in Bosnia and Herzegovina.